Competitiveness Level of Photovoltaic Solar Systems in Ouagadougou (Burkina Faso): Study Based on the Domestic Electric Meters Calibration - Konan Lambert Amani; Raguilignaba Sam; François Zougmoré (International Journal of Photoenergy)
The mean cost price of electricity in Burkina Faso at the end of the last quarter of 2012 was 158 FCFA/kWh for a country where more than 46% of the population lives below the national poverty threshold. To look for solution to that problem, the resort to photovoltaic solar energy is justified for that country. The purpose of this study is to promote the integration of both technical and economical surveys in solar energy preliminary projects in Ouagadougou. To reach that, investigations were carried out in some households and attention was paid from the calibration of the domestic electric meters. Energy demands collected within each household allow us to design a corresponding solar kit through optimization rules. An estimate was edited and financial viability study for each household was also carried out thereafter. In this study, only households using the national electricity network calibration meter on their disadvantage favorably answered to all financial indicators and appear as the only one that could profit from such project. This work is helpful to note that photovoltaic solar energy still stays at a primitive level of competitiveness compared to conventional energy resources for small systems in Ouagadougou.